The Effect of E-Performance Appraisal System and Additional Income of Civil Servant on Performance with Job Satisfaction as Intervening Variable in the Regional Secretarial of Mojokerto City - Widya Windasari (Airlangga Development Journal, 2019)
Since 2019 the Government of Mojokerto City has made efforts to convert the performance appraisal system  manually  into  an  online  system.  This  effort  was  made  to  realize  effective  and  efficient governance  based  on  technology.  E-Performance  is  a  website-based  application  used  by  the Government  of  Mojokerto  City  to  manage  and  assess  employee  performance.  E-Performance  is  a staffing  system  that  can  determine  oversight  to  the  activities  of  civil  servants,  who  can  then  directly determine the amount of the additional income of civil servant. The purpose of this study is to analyze and  prove  the  effect  of  e-performance  appraisal  system  and  additional  income  of  civil  servant  on performance  in  the  Regional  Secretariat  of  Mojokerto  City  with  job  satisfaction  as  an  intervening variable.  This  research  uses  a  quantitative  approach  combined  with  an  explanatory  method.  The results  of  this  study  conclude  several  things,  including:  1.)  E-Performance  appraisal  system  has significant positive effect on performance; 2.) Additional income of civil servant has significant positive effect  on  performance;  3.)  E-Performance  appraisal  system  has  significant  positive  effect  on  job satisfaction; 4.) Additional income of civil servant has significant positive effect on job satisfaction; 5.) Job  satisfaction  has  significant  positive  effect  on  performance;  6.)  E-Performance  appraisal  system and  additional  income  of  civil  servant  have  significant  positive  effect  on  performance  through  job satisfaction.